2010
DOI: 10.1007/978-3-642-10858-7_4
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Polyamines and Inflammation for Cancer Prevention

Abstract: Increased polyamine synthesis and inflammation have long been associated with intraepithelial neoplasia, which are risk factors for cancer development in humans. Targeting polyamine metabolism (by use of polyamine synthesis inhibitors or polyamine catabolism activators) and inflammation (by use of nonsteroidal anti-inflammatory drugs) has been studied for many cancers, including colon, prostate, and skin. Genetic epidemiology results indicate that a genetic variant associated with the expression of a polyamine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 96 publications
(101 reference statements)
1
43
0
Order By: Relevance
“…The polyamine transporter (PAT) is frequently upregulated in many tumor types and is crucial for importing exogenous polyamines [95]. The imaginal disc epithelium of Drosophila has been successfully used to screen PAT-selective molecules [96].…”
Section: Drosophila In Drug Uptake and Bioavailabilitymentioning
confidence: 99%
“…The polyamine transporter (PAT) is frequently upregulated in many tumor types and is crucial for importing exogenous polyamines [95]. The imaginal disc epithelium of Drosophila has been successfully used to screen PAT-selective molecules [96].…”
Section: Drosophila In Drug Uptake and Bioavailabilitymentioning
confidence: 99%
“…Increased polyamine synthesis is associated with inflammation 78 ; thus, polyamines accumulate in infected tissues 79 . More than 60 years ago, it was reported that spermine levels increase at sites of mycobacterial infection and that spermine possesses tuberculostatic activity 80 .…”
Section: Drug Uptake Into M Tuberculosismentioning
confidence: 99%
“…Treatment of colon cancer models and clinical trials with polyamine-metabolism inhibitors have resulted in ambiguous findings (Babbar and Gerner, 2011), however targeting both polyamine production and biofilm interactions could prove to be a more successful strategy.…”
Section: Discussionmentioning
confidence: 99%